Prediksi Perguruan Tinggi Negeri dengan Menggunakan Metode Naive Bayes - Rahmania Aulia Ikrimah Putri; Tacbir Hendro Pudjiantoro (Ikatan Ahli Informatika Indonesia, 2020)
Achievement is the learning outcomes obtained by someone where the ability to increase over time, achievement is not caused by the growth process but with the learning situation. The ability to master knowledge that has been tested for certainty and truth so that it can be measured in the form of grades or what is usually referred to as academic achievement. At least XYZ School students are accepted into state universities. By using the Naive Bayes method, the prediction results are accurate enough to facilitate the Counseling Guidance Section (BK) directing students to register for State Universities (PTN) through the National Higher Education Entrance Entrance Test (SNMPTN).